Lighting Intensity Controller Design Using Node Mcu Esp-8266 - Nurmina Y Rakib; Imam Hizbullah; Zulaeha Mabud (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
Controlling lights using the Internet is one of the uses of the Internet of Things concept. This light intensity control system is an alternative to saving electricity. Currently, the use of smartphones is no stranger to the broader community as well as the use of messaging applications such as Whatsapp. This research develops a prototype that applies the concept of remote control to a light control system and monitors light intensity that utilizes the NodeMCU ESP8266 microcontroller and is also a wifi module and uses a relay instead of a switch and also a servo that maintains light intensity. System control uses a smartphone and Whatsapp application to send commands to the microcontroller. The results of testing this prototype can work and function properly, realizing a remote light control system turns off and turns on the lights and adjusts the light intensity through commands sent via the Whatsapp application.